Normativity of Consumer Protection in the Perspective of Maqāṣid al-Sharīʿah: An Analysis of the Effectiveness of Laws Related to Personal Data Protection in WhatsApp Application Users - Mailiena, Cristine; Tanzilulloh, M Ilham (Institut Agama Islam Negeri Ponorogo, 2024)
Personal data security is the right of every person to protect their personal data confidentially. This research discusses regulations for consumer protection, personal data protection, and their implementation from the perspective of the Maqāṣid al-Sharīʿah. The aim of this research is to determine the extent to which laws related to consumer data protection have been implemented to prevent leaks in the personal data of WhatsApp application users. This study used a qualitative approach with normative empirical research methods. Normative research examines Law No. 8 of 1999 concerning Consumer Protection and Law No. 27 of 2022 concerning Personal Data Protection, while empirical research examines the implementation of these regulations. Researchers draw the conclusion that regulations related to the protection of consumers' personal data and their implementation fall within the concept of Maqāṣid al-Sharīʿah, especially the basic principle of maintaining one's honor (ḥifẓ al-ʿirḍ) because these regulations were made to protect one's privacy.